Cellulose nanocrystal driven crystallization of poly(d, l‐lactide) and improvement of the thermomechanical properties. Issue 10 (30th October 2014) - Camarero‐Espinosa, Sandra; Boday, Dylan J.; Weder, Christoph; Foster, E. Johan
ABSTRACT The technological exploitation of polylactide in fields requiring wide range of operating conditions is limited by the low crystallization rate of the polymer and therewith the low thermomechanical stability. Here we report the crystallization and consequent improvement of the thermomechanical properties of originally amorphous poly(d, l‐lactide) (d : l ratio 11 : 89) loaded with cellulose nanocrystals (CNCs). Isothermal treatment of samples with different CNC contents and at various temperatures, showed up to 6 wt % crystalline phase formation, as confirmed by differential scanning calorimetry and X‐ray diffraction measurements. Under a particular set of annealing conditions, CNCs promote the formation of a lamellar structure. This provides the system with higher order and cohesion which in combination with stress‐transfer between CNCs, led to an increase of the storage modulus in the rubbery plateau up to 30 times (from 2.7 MPa up to 79 MPa), a rise of the melting temperature up to 50°C, and an improvement of the Young's modulus up to 40%. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41607.